Recapitulation of hepatitis B virus–host interactions in liver organoids from human induced pluripotent stem cells - Nie, Yun-Zhong; Zheng, Yun-Wen; Miyakawa, Kei; Murata, Soichiro; Zhang, Ran-Ran; Sekine, Keisuke; Ueno, Yasuharu; Takebe, Takanori; Wakita, Takaji; Ryo, Akihide; Taniguchi, Hideki (EBioMedicine, 2018)
Therapies against hepatitis B virus (HBV) have improved in recent decades; however, the development of individualized treatments has been limited by the lack of individualized infection models. In this study, we used human induced pluripotent stem cell (hiPSC) to generate a functional liver organoid (LO) that inherited the genetic background of the donor, and evaluated its application in modeling HBV infection and exploring virus–host interactions. To establish a functional hiPSC-LO, we cultured hiPSC-derived endodermal, mesenchymal, and endothelial cells with a chemically defined medium in a three-dimensional microwell culture system. Based on cell-cell interactions, these cells could organize themselves and gradually differentiate into a functional organoid, which exhibited stronger hepatic functions than hiPSC derived hepatic like cell (HLC). Moreover, the functional LO demonstrated more susceptibility to HBV infection than hiPSC-HLC, and could maintain HBV propagation and produce infectious virus for a prolonged duration. Furthermore, we found that virus infection could cause hepatic dysfunction of hiPSC-LOs, with down-regulation of hepatic gene expression, induced release of early acute liver failure markers, and altered hepatic ultrastructure. Therefore, our study demonstrated that HBV infection in hiPSC-LOs could recapitulate virus life cycle and virus induced hepatic dysfunction, suggesting that hiPSC-LOs may provide a promising individualized infection model for the development of individualized treatment for hepatitis.